"A whole new future" – identity construction among disadvantaged young adults. Issue 7 (14th November 2016) - Koen, Jessie; Van Vianen, Annelies; Klehe, Ute-Christine; Zikic, Jelena
Abstract : Purpose: The purpose of this paper is to explore how disadvantaged young adults construct a positive work-related identity in their transition from unemployment to employment, and what enables or constrains a successful transition. Design/methodology/approach: The authors conducted semi-structured interviews with 29 apprentices of a reemployment program (Jamie Oliver's Fifteen). The qualitative data were complemented by data on participants' reemployment status one year after the program ended. Findings: Identity construction was not preceded by clear motives or "possible selves." Rather, serendipitous events led to participation in the reemployment program, after which provisional selves seemed to emerge through different pathways. The data also suggested that disadvantaged young adults had to discard their old selves to consolidate their new identity. Research limitations/implications: A successful transition from unemployment to employment may require that old selves must be discarded before new selves can fully emerge. Given that our qualitative design limits the generalizability of the findings, the authors propose a process model that deserves further empirical examination. Practical implications: A clear employment goal is not always required for the success of a reemployment intervention: interventions should rather focus on accommodating the emergence and consolidation of provisional selves. Yet, such programs can be simultaneously effective and unhelpful: especially group identification should be monitored. Originality/value: Most research assumes that people are driven by specific goals when making a transition. The current study shows otherwise: the factors that enable or constrain a successful transition are not to be found in people's goals, but rather in the process of identity construction itself.